STRATEGI DALAM PENINGKATAN JUMLAH NASABAH ASURANSI JIWA DI AJB BUMIPUTERA 1912 MEULABOH - Nuraini Yusuf; Muhammad Ridhwan; Mirna Ria Andini (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2019)
AJB Bumiputera 1912 Meulaboh is an insurance company that has been established for decades until now, it still remains one of the insurance companies that are in demand by the people of Meulaboh. Many products offered by the AJB Bumiputera 1912 Meulaboh is expected to increase the number of life insurance customers and it is is one of the strategies used in the process of increasing the number of insurance customers. As for the results of the study, AJB Bumiputera 1912 followed several stages, namely offering superior products to prospective customers, insurance product price quotes that are tailored to all layers of prospective insurance customers, promotion of insurance products to various prospective insurance customers, the selection of office locations that are very appropriate in the center of Meulaboh City, the selection of employees who work is carried out with a variety of processes in accordance with the applicable operational standards in AJB Bumiputera 1912 throughout Indonesia.